2018
DOI: 10.1007/s00213-018-4865-0
|View full text |Cite
|
Sign up to set email alerts
|

Decrease of cocaine, but not heroin, self-administration and relapse by the tyrosine kinase inhibitor masitinib in male Sprague Dawley rats

Abstract: RationaleAccumulating evidence shows that cocaine, and also heroin, influence several tyrosine kinases, expressed in neurons and in non-neuronal populations such as microglia, astrocytes and mast-cells. Drug-induced activation of mast cells both triggers inflammatory processes in the brain mediated by the glial cells they activate, and facilitates histamine release which may directly influence the dopamine system. Thus, by triggering the activation and degranulation of mast cells dependent on the tyrosine kina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 81 publications
(100 reference statements)
1
15
0
Order By: Relevance
“…This possibility is in line with recent findings demonstrating that systemic administration of the Src/Fyn inhibitor, AZD0530, attenuates goal-directed alcohol self-administration in mice (Morisot et al, 2019). Xie et al previously showed that administration of the Src/Fyn inhibitor PP2 into the dorsal hippocampus attenuates context-dependent cocaine seeking (Xie et al, 2013), and more recently, Belin-Rauscent reported that oral administration of the Src PTKs inhibitor, Masitinib, attenuates selfadministration of cocaine (Belin-Rauscent et al, 2018). Thus, it would be of interest to determine whether Fyn in DMS dMSNs contributes to goal-directed seeking of other drugs of abuse.…”
Section: Discussionsupporting
confidence: 82%
“…This possibility is in line with recent findings demonstrating that systemic administration of the Src/Fyn inhibitor, AZD0530, attenuates goal-directed alcohol self-administration in mice (Morisot et al, 2019). Xie et al previously showed that administration of the Src/Fyn inhibitor PP2 into the dorsal hippocampus attenuates context-dependent cocaine seeking (Xie et al, 2013), and more recently, Belin-Rauscent reported that oral administration of the Src PTKs inhibitor, Masitinib, attenuates selfadministration of cocaine (Belin-Rauscent et al, 2018). Thus, it would be of interest to determine whether Fyn in DMS dMSNs contributes to goal-directed seeking of other drugs of abuse.…”
Section: Discussionsupporting
confidence: 82%
“…In marked contrast, rats with post-training AIC lesions, made once they have reached a plateau of escalated intake (Ahmed et al, 2000;McNamara et al, 2010) that usually remains stable for weeks (McNamara et al, 2010), continued to escalate their intake whereas sham-operated control rats maintained the pre-lesion plateau. The enhanced escalation following AIC lesions was accompanied by an increased propensity to relapse, as measured as a higher rate of responding for the drug under extinction following a brief period of abstinence (Belin-Rauscent et al, 2018). The effects of post-escalation AIC lesions on the further escalation of heroin intake could not be attributable to an effect on body weight, which influences the pharmacokinetic properties of the drug (Rook et al, 2006a;Rook et al, 2006b), or an increased tolerance to the reinforcing properties of heroin since AIC lesioned rats did not differ from sham controls in their increase in body weight following AIC lesions, or in their response to heroin-primed reinstatement of responding after abstinence.…”
Section: Discussionmentioning
confidence: 97%
“…Rats were kept under isoflurane anaesthesia (O 2 : 2 L/min; 5% for induction and 2-3% for maintenance and analgesia (Metacam, 1 mg/kg, sc., Boehringer Ingelheim) and implanted with a home-made indwelling catheter into their right jugular vein as previously described (Belin-Rauscent et al, 2018). Following surgery, rats received daily oral treatment with the analgesic for three days and an antibiotic (Baytril, 10mg/kg, Bayer), which they first received on the day prior to surgery, for a week.…”
Section: Intra-jugular Surgerymentioning
confidence: 99%
See 2 more Smart Citations